Single circulating tumor cell sequencing as an advanced tool in cancer management. (2nd January 2016) - Salvianti, Francesca; Pazzagli, Mario; Pinzani, Pamela
Abstract : Circulating tumor cells (CTCs) shed by the primary tumor and metastases are considered a real-time 'liquid biopsy', reflecting the disease complexity that evolves during progression, showing in its late stages different genetic, epigenetic and expression features. Consequently, heterogeneity and development of characteristic features upon disease progression are the two main goals that emerging technologies should account for in view of a clinical application. Single-cell analysis, now possible due to technological advances, may help elucidate tumor heterogeneity at the CTC level. This review focuses on the necessary steps for the analysis of CTCs at the single-cell level. A concise overview is given on the alternative methods referring in particular to studies on the mutational status of single CTCs from cancer patients.